PENGARUH HARGA CRUDE PALM OIL DUNIA, RETURN EQUITY DAN NILAI TUKAR RUPIAH TERHADAP HARGA SAHAM PT. LONDON SUMATERA INDONESIA PLANTATION Tbk - Miyv Fayzhall (Journal Of Communication Education, 2017)
A B S T R A C T This research is conducted to know the influence of of a number of factors associated with the stock price of PT. London Sumatera Indonesia Plantation Tbk. These factors include the price of crude palm oil (CPO) and financial ratios such as return on equity and exchange rate hereinafter in this study functioned as independent variables to predict the stock price which functioned as the dependent variable. Implementation of this research takes 2 months ie June 2016 - July 2016 includes designing, implementing, and reporting the results. This study uses ex post facto design using data that has been formed before the research was conducted. The population of this research is all around the Financial Statements PT. London Sumatera Indonesia Plantation Tbk since the company established to run the company until today. The study sample set of 32 samples, the quarterly financial statements for the period 2008-2015, the period of study for 8 (eight) years obtained through purposive sampling technique. Results showed that simultaneous independent variable prices of crude palm oil (CPO), Return on Equity and Exchange rate significant impact on the price of PT. London Sumatera Indonesia Plantation Tbk. Partially independent variable prices of crude palm oil (CPO), Return on Equity and Exchange rate significant positive effect on stock price. For the coefficient of determination R2, the third independent variable Price of Crude Palm Oil (CPO), Return on Equity and Exchange rate variable can explain stock price by 82.44% while the remaining 17.56% is explained by other variables outside of this research.